Implementation of the Turbo Boyer Moore Algorithm in Searching Medical Record Data - Victor Yonathan Gultom; Yupianti Yupianti; Prahasti Prahasti (Jurnal Komputer, Informasi dan Teknologi, 2021)
The Patient Medical Record Data Search application is used to assist the Bintunan Air Treatment Health Center in finding medical record data with faster time efficiency, where so far the search is still done manually by looking at the books. The Patient Medical Record Data Search application is used to assist the Puskesmas in managing patient data, doctor data and patient medical record data every time for treatment, so that the processed data is stored in the application database. Applications for Searching Patient Medical Record Data at the Bintunan Air Treatment Health Center have implemented one of the search algorithms, namely the Turbo Boyer Moore algorithm, where the search process is carried out per string / word through a shift in data matching between keywords and data in the database. Based on the results of black box testing, the functionality of the Patient Medical Record Data Search Application at the Bintunan Water Treatment Health Center has been running properly and is able to display medical record search results using the Turbo Boyer Moore Algorithm.